Glioblastoma extracellular vesicles: reservoirs of potential biomarkers - Redzic JS; Ung TH; Graner MW (Dove Medical Press, 2014)
Jasmina S Redzic,1 Timothy H Ung,2 Michael W Graner2 1Skaggs School of Pharmacy and Pharmaceutical Sciences, 2Department of Neurosurgery, School of Medicine, University of Colorado Denver, Aurora, CO, USA Abstract: Glioblastoma multiforme (GBM) is the most frequent and most devastating of the primary central nervous system tumors, with few patients living beyond 2 years postdiagnosis. The damage caused by the disease and our treatments for the patients often leave them physically and cognitively debilitated. Generally, GBMs appear after very short clinical histories and are discovered by imaging (using magnetic resonance imaging [MRI]), and the diagnosis is validated by pathology, following surgical resection. The treatment response and diagnosis of tumor recurrence are also tracked by MRI, but there are numerous problems encountered with these monitoring modalities, such as ambiguous interpretation and forms of pseudoprogression. Diagnostic, prognostic, and predictive biomarkers would be an immense boon in following treatment schemes and in determining recurrence, which often requires an invasive intracranial biopsy to verify imaging data. Extracellular vesicles (EVs) are stable, membrane-enclosed, virus-sized particles released from either the cell surface or from endosomal pathways that lead to the systemic release of EVs into accessible biofluids, such as serum/plasma, urine, cerebrospinal fluid, and saliva. EVs carry a wide variety of proteins, nucleic acids, lipids, and other metabolites, with many common features but with enough individuality to be able to identify the cell of origin of the vesicles. These components, if properly interrogated, could allow for the identification of tumor-derived EVs in biofluids, indicating tumor progression, relapse, or treatment failure. That knowledge would allow clinicians to continue with treatment regimens that were actually effective or to change course if the therapies were failing. Here, we review the features of GBM EVs, in terms of EV content and activities that may lead to the use of EVs as serially accessible biomarkers for diagnosis and treatment response in neuro-oncology. Keywords: exosomes, microvesicles, brain tumors, proteomics, lipidomics, ribonomics